Structural properties of functions defined on a sphere on the basis of Φ-strong approximation - Lasuriya, R. A. (Ukrains’kyi Matematychnyi Zhurnal, 2006)
Structural properties of functions defined on a sphere are determined on the basis of the strong approximation of Fourier-Laplace series.